Behavior of precast CECFST column-to-column connection under compression - Lim, Jun Guang (Nanyang Technological University, 2022)
This paper studies the compressive behaviour of precast concrete-encased concrete-filled steel tubular (CECFST) columns. An experimental programme was conducted on three precast CECFST column-to-column connections and one cast-in-place (CIP) connection under axial and uniaxial eccentric compression. The test results including ultimate failure loads, load-strain curves, and failure modes were presented. It was found that the peak load, maximum moment, and displacement ductility of precast CECFST columns were higher than CIP CECFST columns. A simplified method containing simplified stress distributions and simplified formulas for predicting the cross-section resistance of precast CECFST column-to-column connection was proposed. The test results and the predicted strength were then used to evaluate the applicability of EN 1994-1-1 on the precast connection, and generally, good agreement was achieved. Finally, a general design approach for the precast connection was developed.